Eco-anxiety and environmental identity in older adults from New Zealand : an exploration of data from the New Zealand health, work and retirement study : a thesis submitted to Massey University in partial fulfilment of the requirements for the degree of Master of Public Health, Massey University - Garrett, Monica Katherine (Massey University, 2026)
Biodiversity and the natural environment are two key determinants of human health. Among other things, they are essential to supporting food security and freshwater availability, and limiting the spread of zoonotic diseases. These determinants face the substantial anthropogenic threats of biodiversity loss, pollution and climate change, which together comprise the triple planetary crisis. Widespread adoption of pro environmental behaviours (PEBs) is one element of the response required to mitigate these threats. Eco-anxiety and environmental identity are two concepts that relate to people’s commitment to PEBs. These concepts have been included in the New Zealand Health, Work and Retirement (NZHWR) Study for the first time in the 2024/25 survey, through the inclusion of the Hogg Eco-Anxiety Scale (HEAS) and the Revised Environmental Identity Scale (R-EID). This thesis includes both a scoping review and a quantitative analysis. The scoping review explores the existing scales used to quantify eco-anxiety and environmental identity in adults (aged 18 and over); the average scores and demographic trends of these scales; and evidence of a relationship between the two concepts. The quantitative analysis explores HEAS and R-EID data from the 2024/25 NZHWR Study, the participants of which are older adults (aged 55 and over) living in New Zealand. This research is the first to quantify eco-anxiety and environmental identity among older adults in New Zealand. Ultimately, this research may help to inform population-level strategies to encourage the adoption of PEBs and, therefore, support biodiversity and the natural environment as important determinants of health.
Keywords: 520304 Health psychology